A case of complete testicular feminisation and 47,XXY karyotype. - Gerli, M (1979)
A very rare case of complete testicular feminisation with a 47,XXY sex chromosome complement is described. The X-chromatin is positive. The subject studied, who belongs to a family in which four other members have Morris's syndrome and have a 46,XY karyotype, is a perfect phenotypic female. The endocrine situation is unique and resembles, in part, that of subjects with Klinefelter's syndrome.